Initiatives related to truth and reconciliation in Montenegro: A general overview - Radević Radomir (Temida, 2004)
Concerning the current initiatives for truth and reconciliation, there are no either state nor any other formal institutions (such as commissions or council for truth and reconciliation) which would deal with this problem in Montenegro in more strategically, fundamental and long-lasting way. There are also no indications that such institutions will be established in the near future. It is completely evident that there is a lack of, at first place, political will in Montenegro for starting these processes. Current initiatives for truth and reconciliation in Montenegro are either projects of individuals or certain NGOs, which are most often reflection of personal need or wish for the truth to be found out or announced and processes finally started, or parts of some other projects or programs.